Science Process Skills Characteristics of Junior High School Students in Lampung - Sunyono, Sunyono (European Scientific Journal, ESJ, 2018)
The quality of international education is measured through PISA and TIMSS results and the member countries are very concerned about their students' ability to work on PISA and TIMSS. Countries with low PISA and TIMSS ratings indicate that students' science process skills in this country are low, including in Indonesia. Therefore, this research needs to be done to see the characteristics of science process skill (SPS) of junior high school students, especially in Indonesia. This study involved 9th-grade students of the academic year 2016/2017 in three randomly selected districts. The number of subjects involved in the study was 120 randomly selected respondents. The research was conducted by survey method, by giving SPSs questions to respondents. The results showed that the SPS of junior high school students in Lampung Province-Indonesia is low. Students from schools in the capital and school areas close to the provincial capitals have the characteristics of SPSs on "observing" and "classifying" indicators in the "moderate" category. Students from distant areas of the provincial capitals, the characteristics of their SPSs are "low", for all indicators (observing, classifying, predicting, interpreting, and communicating).